Team diversity and new product development performance in manufacturing sector: A conceptual framework - Mohd Zaki, Nor Hazwani; Othman, Siti Norezam (2013)
In achieving high new product development performance, new product development team was playing the important roles. People were important in performing a team to develop new product. Different background of team members was vital to ensure high new product development performance. Diversity of team members not only should be focusing on their functional diversity, also team members’ experiences in new product development process should be considered. Team who did not have experienced people tends to achieve low new product development performance. Therefore, this paper presented a conceptual framework assuming that diversity of team members in terms of functional diversity and team members’ experiences gave significant effects to new product development performance. This study also suggested that to investigate the relationships through empirical data of various industries in manufacturing sector in Malaysia.